Types of Fluid Alteration and Developing Mechanism of Deep Marine Carbonate Reservoirs - Dongya Zhu; Quanyou Liu; Juntao Zhang; Qian Ding; Zhiliang He; Xuefeng Zhang (Geofluids)
Accurate recognition of the types of alteration fluid and the development mechanisms are important concerns in studying deep marine carbonate reservoirs. Major fluid types, such as seawater, meteoric water, deep burial formation water, hydrothermal fluid, and thermochemical sulfate reduction- (TSR-) derived fluid, were identified based on carbon, oxygen, and strontium isotope compositions of many samples from the Tarim, Sichuan, and Ordos basins in China. Compared with normal marine limestones, seawater calcite cement has similar isotopic compositions. Calcite cement precipitated from meteoric water has extremely light oxygen isotope compositions, and its δ18OV-PDB reaches -18.8‰. Due to the fractionation of oxygen isotopes at high temperatures (101.2~145.6°C), calcite precipitated from deep burial formation water and deep hydrothermal fluid has moderately light oxygen isotope compositions. The TSR process consumes organic matter to produce CO2/CO32-, and the calcite from TSR-derived fluid has very light carbon isotopes (δ18OV-PDB, -18.9‰) due to the incorporation of organic CO2/CO32-. Formation water and TSR-derived fluid generally originate and are confined within the carbonates and are consequently termed endogenous fluids. The 87Sr/86Sr ratios of calcite cements from endogenous fluids are basically the same as those of surrounding carbonates. Meteoric water and hydrothermal fluid originate outside the carbonate strata and are exogenous fluids. The 87Sr/86Sr ratios of calcite cements from exogenous fluids are higher than those of surrounding carbonates, up to 0.710558. For karst carbonate reservoirs developed in tectonic uplift-meteoric water environments, the reservoir spaces of karst caves and fractures occur principally under and near unconformity surfaces and megacrystalline calcite cements occur below the karst zone. In deep fault-hydrothermal fluid environments, high-quality carbonate reservoirs develop downward into ultradeep strata. In deep burial-TSR-derived fluid environments, dissolution porosity can be well preserved for a long geological time due to high CO2 and H2S concentrations.